HOW DOES THE WRITER SAVE THE READER'S FACE? (Descriptive Study at Using Face Concept in Politeness Strategy in some Notices in Singapore) - Siti Suharsih (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2015)
Giving command to other people should consider many things: choice of word, context of situation and social context. Those can help us, both as speaker or writer, avoid the rudeness and threaten other's face. This paper is intended to take term "politeness" into account within some examples of sentences formed in notices. The samples are taken from two different places in Singapore: in a guest house and in mosque. Those notices are analyzed using "face" concept by showing the strategy used by the writer in both places. The result shows the writers from the two places use different strategy in commanding the reader. At guests house, the writer uses indirectness and give positive face to the reader. In this point, the writer tries to be close to the reader, decrease the distance between them. In the other side, the notices found in a mosque use imperative sentence. This form of sentence contains directive, asking the reader to do something directly. Based on the form and content of sentences in those notices, the readers will be potentially threatened. For that reason, the writer does FTA in most of notices.